PENINGKATAN KEMAMPUAN LISTENING COMPETENCE MENGGUNAKAN INSTRUCTIONAL IMPERATIVE DALAM BIDANG BISNIS DIGITAL PADA SISWA SMK DI KABUPATEN SEMARANG - Hardiany, Dewi; Susilowati, Endang; Siswati, Ari (Universitas Ngudi Waluyo, 2023)
Community Service Activities (PkM) to improve Listening Competence skills using Instructional Imperatives for students of SMK Muhammadiyah Ungaran Semarang Regency are carried out to improve listening skills in English, especially those that are appropriate to the field of digital business. The background of this activity is to overcome the problem of students' low ability in listening competence in English due to inappropriate learning methods. Learning methods that are less developed and carried out rigidly lead to boredom in learning. Generating willingness and interest in English is one of the tasks and challenges for English teachers. In addition, this PkM activity also aims to increase students' interest in English with material that is applicable and in accordance with student majors in business class. The implementation of the activity begins with socialization and briefing for Ngudi Waluyo University students who will be involved in this activity, followed by coordination with the target school regarding the implementation schedule. It ends with reporting the results of activities after the implementation of the program is complete. Community service activities in the form of Improving Listening Competence with the instructional imperative method for High School Level Students in Semarang Regency in Class X SMK Muhammadiyah Ungaran provide benefits for students, namely being able to understand audio in English more easily. This ability is needed by students. Students will find it easier to understand reading by using the right method. The next stage of this activity is to follow up on the results of the activity, then evaluate the limitations and weaknesses of the method and plan activities to develop students' listening competence by using other methods. Keywords: Listening competence, instructional imperative, bussiness digital